Developing a cosmetic series: Results from the ESSCA network, 2009‐2018. (29th September 2020) - Horton, Emma; Uter, Wolfgang; Geier, Johannes; Ballmer‐Weber, Barbara; Bauer, Andrea; Bircher, Andreas; Dickel, Heinrich; Giménez‐Arnau, Ana; Gonçalo, Margarida; John, Swen Malte; Mahler, Vera; Schuttelaar, Marie L. A.; et al.
Abstract: Background: There is considerable variability across European patch test centres as to which allergens are included in local and national cosmetics series. Objectives: To propose a standardized, evidence‐based cosmetic series for Europe based on up‐to‐date analysis of relevant contact allergens. Methods: We collated data from the European Surveillance System on Contact Allergies (ESSCA) from 2009 to 2018 to determine which cosmetic allergens produce a high yield of contact allergy. Contact allergens with a prevalence of >0.3% that were considered relevant were included. Rare contact allergens were excluded if deemed no longer relevant or added to a supplemental cosmetic series for further analysis. Results: Sensitization prevalences of 39 cosmetic contact allergens were tabulated. Thirty of these allergens yielded >0.3% positive reactions and are therefore included in our proposed European cosmetic series. Six were considered no longer relevant and therefore excluded. Three were included in a supplementary European cosmetic series. An additional nine allergens were included in either the core or supplemental European cosmetic series following literature review. Conclusion: We have derived a potential European cosmetic series based upon the above methods. This will require ongoing investigation based upon the changing exposure profiles of cosmetic allergens as well as new and evolving substances.